Human Brain–Derived Neurotrophic Factor Gene-Modified Bone Marrow Mesenchymal Stem Cells Combined With Erythropoietin Can Improve Acute Spinal Cord Injury. Issue 1 (27th March 2020) - Li, YongLei; Wang, Hongchen; Ding, Xiaofang; Shen, Jiancheng; Zhou, Haitao; Jiang, Dengxue; Jin, Chen; Li, Kuang
Objective: To assess the effect as well as mechanism of bone marrow mesenchymal stem cells (BMSCs) modified by the human brain–derived neurotrophic factor gene combined with erythropoietin (EPO) in the treatment of acute spinal cord injury (SCI) in rats. Methods: The Brain-derived neurotrophic factor (BDNF) gene was transected by a virus vector. Rats with SCI were randomly split into following groups: The normal saline (NS) group, the EPO group, The Basso, Beattie, and Bresnahan scores, messenger RNA BDNF expression, and apoptosis rates were compared between the 4 groups at 1, 3, 7, 14, and 21 days after SCI. Results: At 7, 14, and 21 days after operation, the expression of the BDNF gene in the other 3 groups was higher than that of the NS group, and the difference was statistically significant ( P < .05). The apoptosis rate in the combined group was less than that of NS, EPO, and BDNF/BMSC groups, and the differences were statistically significant ( P < .05). Conclusion: Brain-derived neurotrophic factor gene-modified BMSC transplantation combined with EPO can promote the repair of nerve function after SCI in rats.